FACTORS INCREASING THE RISK OF RECURRENCE IN FISTULA IN ANO - Minahil Hashmi; Tousif Ahmed; Alvina Khan; Dharmoon Arija; Mujahid ur Rehman; Syed Mufeez Uddin Ahmed (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
BACKGROUND: An anal fistula, also known as a fistula in ano, is a passage that forms, connecting the anal canal or rectum to the skin surrounding the anus. The primary cause of anorectal fistulas is typically an infection in the anorectal region. The key elements of treating an anal fistula involve the closure of the internal opening of the fistula tract, the drainage of infection or necrotic tissue, and the surgical removal of the fistulous tract while ensuring the preservation of sphincter function. OBJECTIVE: The objective of this research was to assess multiple facets, including intraoperative complications, postoperative complications, and various factors linked to the recurrence and treatment of anal fistulas. This assessment encompassed procedures such as fistulotomy, fistulectomy, the use of setons, and the application of an anal advancement flap. METHODOLOGY: A retrospective cohort study was undertaken at Dr. Ziauddin Hospital in Karachi spanning the period from 2018 to 2022. The study determined the sample size, and a total of 130 individuals were enrolled for analysis. Data analysis was performed using SPSS, encompassing both quantitative and qualitative data. RESULT: The average age at which individuals presented with fistula in ano was 38 years (with a standard deviation of ± 10.32), ranging from 18 to 60 years. Notably, there was a statistically significant correlation with recurrence, as indicated by a p-value of 0.022. Furthermore, the study had a greater representation of males than females, but this gender difference did not yield any statistically significant association (p-value = 0.706).The type of surgical procedure performed and the presence of comorbidities were found to be significantly linked to the recurrence of fistulas, with p-values of 0.00 and 0.01, respectively. CONCLUSION: Fistulotomy and fistulectomy exhibited lower recurrence rates in comparison to the use of setons. Furthermore, the presence of comorbid conditions like diabetes and hypertension, as well as age, were identified as significant factors associated with the recurrence of fistulas.